Dynamic Alterations to α-Actinin Accompanying Sarcomere Disassembly and Reassembly during Cardiomyocyte Mitosis. - Xiaohu Fan; Bryan G Hughes; Mohammad A M Ali; Woo Jung Cho; Waleska Lopez; Richard Schulz (PLoS ONE, 2015)
Although mammals are thought to lose their capacity to regenerate heart muscle shortly after birth, embryonic and neonatal cardiomyocytes in mammals are hyperplastic. During proliferation these cells need to selectively disassemble their myofibrils for successful cytokinesis. The mechanism of sarcomere disassembly is, however, not understood. To study this, we performed a series of immunofluorescence studies of multiple sarcomeric proteins in proliferating neonatal rat ventricular myocytes and correlated these observations with biochemical changes at different cell cycle stages. During myocyte mitosis, α-actinin and titin were disassembled as early as prometaphase. α-actinin (representing the sarcomeric Z-disk) disassembly precedes that of titin (M-line), suggesting that titin disassembly occurs secondary to the collapse of the Z-disk. Sarcomere disassembly was concurrent with the dissolution of the nuclear envelope. Inhibitors of several intracellular proteases could not block the disassembly of α-actinin or titin. There was a dramatic increase in both cytosolic (soluble) and sarcomeric α-actinin during mitosis, and cytosolic α-actinin exhibited decreased phosphorylation compared to sarcomeric α-actinin. Inhibition of cyclin-dependent kinase 1 (CDK1) induced the quick reassembly of the sarcomere. Sarcomere dis- and re-assembly in cardiomyocyte mitosis is CDK1-dependent and features dynamic differential post-translational modifications of sarcomeric and cytosolic α-actinin.